Case report: Anti-NMDA receptor encephalitis manifesting as rapid weight loss and abnormal movement disorders with alternating unilateral ptosis and contralateral limb tremor - Han, Yue; Gong, Sizhu; Wan, Yafei; Fu, Xiyao; He, Enling; Liu, Min; Deng, Fang (Frontiers in Immunology, 2022)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, associated with immunoglobulin G (IgG) autoantibodies against the GluN1 subunit of the NMDAR, is one of the most common types of autoimmune encephalitis. In patients with anti-NMDAR encephalitis, movement disorders (MDs) are often frequent, mainly presenting as facial dyskinesias and stereotyped movements. The alternating clinical manifestation of limb tremor with unilateral ptosis is rare. Here, we report an interesting case of a 22-year-old woman with rapid weight loss presenting with staged dyskinesia. Interestingly, she typically showed persistent tremor of the right upper limb, which would stop when her left upper eyelid drooped uncontrollably, a phenomenon that lasted for a few seconds, followed by automatic upper eyelid lift and continued persistent tremor of the upper limb. Moreover, it was fortunate to find anti-NMDAR antibodies in her cerebrospinal fluid (CSF), which indicated the patient had anti-NMDAR encephalitis. And abnormal apparent diffusion coefficient (ADC) hyperintense signals on the left midbrain interpeduncular fossa explained this manifestation of focal neurological deficit. After the systematic administration of immunotherapy (intravenous immunoglobulin, IVIG), steroid pulse therapy, and symptomatic treatment, the initial symptoms were significantly relieved except for limb tremor. The MDs were becoming less visible for the next six months under topiramate prescriptions. Noteworthy, there are no specific MD phenotypes in anti-NMDAR encephalitis. We describe the young women with unique MDs and rapid weight loss to help us get a more comprehensive understanding of anti-NMDAR encephalitis.